Data from: Bottom-up trait-mediated indirect effects decrease pathogen transmission in a tritrophic system - Elderd, Bret D. (Dryad, 2018)
A plant's induction of secondary defenses helps to decrease herbivore
damage by changing resource quality. While these chemical or physical
defenses may directly decrease herbivory, they can also have indirect
consequences. In a tritrophic system consisting of a plant, an insect
herbivore, and an insect pathogen, plant based trait-mediated indirect
effects (TMIEs) can alter host-pathogen interactions and, thereby,
indirectly affect disease transmission. In a series of field experiments,
individual soybean plants (Glycine max) were sprayed with either a
Jasmonic Acid (JA) solution to trigger induction of plant defenses or a
similar control compound. Fall armyworm (Spodoptera frugiperda) larvae
along with varying amounts of a lethal baculovirus were placed on the
plants to measure transmission. Induction of plant defenses decreased
viral transmission due to increased population heterogeneity arising from
changes in individual susceptibility. The change in susceptibility via
TMIEs was driven by a decrease in feeding rates and an increase viral dose
needed to infect larvae. While the induction against herbivore attack may
decrease herbivory, it can also decrease the efficacy of the
herbivore's pathogen potentially to the plant's detriment. While
TMIEs have been well-recognized for being driven by top-down forces,
bottom-up interactions can dictate community dynamics and, here, epizootic
severity.
Bottom-up trait-mediated indirect effects decrease pathogen transmission
in a tritrophic systemZip file consisting of three comma delimited (csv)
files that contain: 1) host-pathogen transmission data; 2) dose-response
data; and, 3) preference data. The first row of the file contains the
column headings associated with the
data.Elderd-BottomupPathogenTransmission.zip
Keywords: Induced plant defenses; Variability in transmission rate; Spodoptera frugiperda multicapsid nucleopolyhedrovirus (SfMNPV); Fall armyworm; Spodoptera frugiperda; Epizootics; baculovirus; bayesian analysis; Glycine max